PENGARUH KARAKTERISTIK PERSONAL, KARAKTERISTIK USAHA, KARAKTERISTIK KREDIT, DAN JAMINAN TERHADAP TINGKAT PENGEMBALIAN KREDIT DI BPR NUSAMBA ADIWERNA KABUPATEN TEGAL TAHUN 2016 - Ika Kusumaningtyas (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2017)
Bank Perkreditan Rakyat (BPR) is one of the spine in national development. There is still have credit problem being an dilemmatic things for bank, in one side want to help the weak society who need modal for their business, in the other side the bank expects a profit from the credit activity for to finance the sustainably BPR Nusamba in Tegal District. Therefore, do the factors analysis which influence credit development levels. The aims of this research are 1) to know about the influence of business characteristic to credit repayment level; 2) to know the influence of credit characteristic to credit repayment level; 4) to know the influence of guarantee required to credit repayment level; 5) to know the influence personal characteristic, business characteristic, credit characteristic, and guarantee simultaneously to credit repayment level. Respondent of this research are from 100 people. The respondent are the customer of BPR NusambaAdiwernaTegal District in 2016 and sample take by using accidental random sampling technique. Result of this research prove that the age is doesn’t influence the fluencyof repayment, education level influential in significant to repayment level, the number of dependents doesn’t influence to credit repayment level. The other result prove that the business profit significantly influence to credit repayment level, the period of business doesn’t influence to credit repayment level, business asset doesn’t significantly influence to credit repayment level. From this research can be find that the loan frequency doesn’t significantly influence to credit repayment level, the other credit doesn’t significantly influence to credit repayment level , obligation per month significantly influence to credit repayment level, and guarantee level is significantly influence to credit repayment level. Therefore, this research also prove that personal characteristic, business characteristic, credit characteristic, and guarantee simultaneously are significantly influence to credit repayment level. Keywords: personal characteristic, business characteristic, credit characteristic, guarantee, credit repayment level.